Sagittal Realignment Following Decompression for Lumbar Spinal Stenosis in Elderly Patients: A Comprehensive EOS Imaging Analysis - Hyung-Youl Park; Ho-Young Jung; Geon-U Kim; Se-Heon Lee; Jun-Seok Lee (Diagnostics)
Background/Objectives: This study investigated whether decompression surgery for lumbar spinal stenosis can effectively improve sagittal alignment in elderly patients. With the growing focus on sagittal balance in spinal surgery, this study aimed to evaluate post-decompression alignment changes and identify the factors influencing these changes using the EOS imaging system. Methods: A retrospective analysis was conducted on 49 elderly patients who underwent decompression surgery alone for lumbar spinal stenosis. Radiologic parameters, measured using the EOS system, and clinical outcomes were assessed preoperatively, at two weeks postoperatively, and at one year postoperatively. Patients were grouped based on the improvement of the sagittal vertical axis (SVA) by 25 mm or more. A multivariate analysis was performed to identify factors affecting sagittal alignment changes. Results: Significant sagittal alignment improvements were observed postoperatively, including a notable increase in thoracic kyphosis and a decrease in SVA observed at one year. Clinical outcomes, such as the Oswestry disability index (ODI) and EQ-5D, significantly improved at both two weeks and one year postoperatively compared to preoperative values (all p-values < 0.05). Multivariate analysis revealed that greater preoperative SVA and higher ODI were significant predictors of sagittal alignment changes (odds ratio [OR] for SVA = 1.014, OR for ODI = 1.034). Conclusions: Decompression surgery for lumbar spinal stenosis in elderly patients can result in significant improvements in sagittal alignment and clinical outcomes. The study suggests that decompression alone is a viable surgical option for elderly patients, particularly those with a greater preoperative sagittal imbalance and disability, even in the absence of major deformities.